2014
DOI: 10.1111/ecc.12256
|View full text |Cite
|
Sign up to set email alerts
|

Neodymium yttrium-aluminium-garnet laser resection significantly improves quality of life in patients with malignant central airway obstruction due to lung cancer

Abstract: Neodymium yttrium-aluminium-garnet (Nd : YAG) laser resection is one of the mostly used interventional pulmonology techniques for urgent desobstruction of malignant central airway obstruction (CAO). The major aim of this trial was to evaluate potential influence of Nd : YAG laser resection on overall quality of life (QoL) in patients with central lung cancer. Patients with malignant CAO scheduled for Nd : YAG laser resection were prospectively recruited in the trial. All patients were given European Organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…It is particular effective for intraluminal and mixed type airway obstruction and less suitable for extraluminal compression (40). In additional to constant and immediate effect in tumor shrinkage, the quality of life and overall health are also improved significantly in patients with malignant central airway obstruction due to lung cancer (41). Although laser monotherapy is quite effective in alleviating symptoms from malignant central airway obstruction, survival benefit will be improved when it combined with multimodal adjuvant therapy (including brachytherapy, chemotherapy, radiotherapy, stenting, chemoradiotherapy) (42).…”
Section: Lasermentioning
confidence: 99%
“…It is particular effective for intraluminal and mixed type airway obstruction and less suitable for extraluminal compression (40). In additional to constant and immediate effect in tumor shrinkage, the quality of life and overall health are also improved significantly in patients with malignant central airway obstruction due to lung cancer (41). Although laser monotherapy is quite effective in alleviating symptoms from malignant central airway obstruction, survival benefit will be improved when it combined with multimodal adjuvant therapy (including brachytherapy, chemotherapy, radiotherapy, stenting, chemoradiotherapy) (42).…”
Section: Lasermentioning
confidence: 99%
“…Among traditional laser therapies, the neodymium yttrium–aluminum–garnet laser is one of the most used techniques for tumor debulking and urgent de-obstruction, and shows an improvement in OS and quality of life. 28 , 29 In contrast, it is proposed that radiotherapy improves the risk of pulmonary function injury and pneumonia, and both local recurrence and toxicity occur late after radiotherapy in patients with central tumors. 30 32 As the result of our study, it is suggested that radiotherapy is more appropriate for nonsurgical patients, but not helpful to surgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of endobronchial therapies are performed in the management of lung cancer [8] , [9] , [10] , [11] , [12] such as photodynamic therapy [13] , [14] , [15] , high-dose-rate brachytherapy [15] , [16] , [17] , [18] , [19] , [20] , [21] , electrocautery [22] , APC [4] , [23] , neodymium yttrium-aluminium-garnet (Nd-YAG) laser therapy [24] , [25] , and cryotherapy [26] . These methods have been used for both the palliation of obstructing inoperable lung cancers in combination with [18] , [21] or after EBRT [16] , and primary treatment of early-stage radiographically occult non-small cell lung cancer [17] .…”
Section: Discussionmentioning
confidence: 99%